Pengaruh Gaya Hidup Dan Perceived Ease Of Use Terhadap Keputusan Mahasiswa Menggunakan Mobile Banking Yang Dimediasi Sikap Pengguna - Salsabila Linnatunnisa; Rini Safitri (Fakultas Ekonomika dan Bisnis Universitas Selamat Sri, 2022)
Advances in mobile technology have grown rapidly to support daily activities. This makes banks required to innovate by changing services to digital-based ones. This study aims to determine how lifestyle and perceived ease of use can affect the decision to use Mobile Banking which is mediated by user attitudes. This type of research is quantitative research. The object of research used in this study were students using Mobile Banking in Malang City as many as 85 respondents. The sampling technique used was convenience sampling technique. Data collection techniques through the distribution of questionnaires. The data analysis technique uses Path Analysis with the help of SPSS software. The variables to be studied are lifestyle (X1), perceived ease of use (X2), user attitudes (Z), and decisions to use Mobile Banking (Y). The results showed that lifestyle partially had a positive effect on user attitudes, partially perceived ease of use had a positive effect on user attitudes, lifestyle partially had a positive effect on decisions to use Mobile Banking, perceived ease of use had no effect on decisions to use Mobile Banking, and the attitude of the user partially has a positive effect on the decision to use Mobile Banking.